33.3L: Late‐News Paper: Optimizing Nanostructures to Enhance Optical Outcoupling of OLED Microdisplays. Issue 1 (1st July 2013) - Pfeifer, Richard; Fehse, Karsten; Vogel, Uwe; Leo, Karl
Abstract We present optical simulations of a nanostructured OLED‐anode design to enhance the optical outcoupling efficiency. The design allows for the integration of a grating structure with high refractive index contrast into top‐emitting OLED microdisplays using CMOS‐compatible techniques.